On (p,q)-Analogue of Gamma Operators - Wen-Tao Cheng; Wen-Hui Zhang (Journal of Function Spaces)
In this paper, a kind of new analogue of Gamma type operators based on (p,q)-integers is introduced. The Voronovskaja type asymptotic formula of these operators is investigated. And some other results of these operators are studied by means of modulus of continuity and Peetre K-functional. Finally, some direct theorems concerned with the rate of convergence and the weighted approximation for these operators are also obtained.